(untitled) (Dandao Xuebao/Journal of Ballistics, 2023)
To study the characteristics of rotation angular acceleration for spin-stabilized projectiles, based on the simplified differential equation which describing the rolling motion and mass-point ballistics equation in exterior ballistics, the expressions of the first and the second derivatives of the rotation angular acceleration were derived. The ballistics characteristics of several typical spin-stabilized projectiles were analyzed and calculated. The results show that the conditions for the first derivatives of the roll acceleration becoming zero can be satisfied in the descending trajectory under the certain parameter combination of aerodynamics, flight status and the configuration parameters of the projectile. Meanwhile, the extreme point of the rotation angular acceleration curve appears at this point. For most cases, there is no extreme point for the roll acceleration curve on the descending trajectory when the elevation angle of the projectile is relatively small(e.g., less than 20°).